Liquidity standards and the value of an informed lender of last resort - Santos, João A.C.; Suarez, Javier (Journal of Financial Economics, 2019)
We consider a dynamic model in which receiving support from the lender of last resort (LLR) may help banks to weather investor runs. We show the need for regulatory liquidity standards when the underlying social trade-offs make the uninformed LLR inclined to support troubled banks during a run. Liquidity standards increase the time available before the LLR must decide on supporting the bank. This facilitates the arrival of information on the bank’s financial condition and improves the efficiency of the decision taken by the LLR, a role that can be modified but not replaced with the use of capital regulation.